2012
DOI: 10.11106/jkta.2012.5.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent Parathyroidectomy during Thyroid Surgery for Papillary Thyroid Carcinoma and Postoperative Hypocalcemia

Abstract: Background and Objectives:The aim of this article is to report our experience of inadvertent parathyroidectomy during thyroid surgery and to analyze its associated factors and clinical implications. In addition, we attempted to determined causative factors that result in permanent hypocalcemia after thyroid surgery. Materials and Methods: We performed a retrospective review of 500 patients who underwent thyroid surgery for the treatment of papillary thyroid carcinoma from 2004 to 2008. Results: Inadvertent par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…[ 17 ] Univariate analysis of our results indicated that total thyroidectomy, although positively correlated ( P = .016) with increased incidence of parathyroidectomy, was not an independent risk factor in multivariate analysis. In contrast to previous reports, [ 18 ] in our study, preoperative diagnosis of malignant disease, duration of the disease prior to thyroidectomy, and concomitant CND were significantly correlated with increased risk of incidental parathyroidectomy in multivariate analysis. However, preoperative diagnosis of malignancy was also found to be an independent predictor by some of the most recent related reviews.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 17 ] Univariate analysis of our results indicated that total thyroidectomy, although positively correlated ( P = .016) with increased incidence of parathyroidectomy, was not an independent risk factor in multivariate analysis. In contrast to previous reports, [ 18 ] in our study, preoperative diagnosis of malignant disease, duration of the disease prior to thyroidectomy, and concomitant CND were significantly correlated with increased risk of incidental parathyroidectomy in multivariate analysis. However, preoperative diagnosis of malignancy was also found to be an independent predictor by some of the most recent related reviews.…”
Section: Discussioncontrasting
confidence: 99%
“…Even for highly-experienced surgeons, inadvertent parathyroid excision has been reported to be up to 15% of thyroidectomy cases. Moreover, the incidence of temporary hypoparathyroidism is up to 46% and that of permanent hypoparathyroidism is up to 6.6% after total thyroidectomy (3,20).…”
Section: Icg Fluorescence Imaging Of Normal Pgsmentioning
confidence: 99%
“…Although various procedures have been introduced to preserve the parathyroid glands, they have not been widely applied because they are what to be gained from the long experience [4][5][6]. After surgery, 46% of patients experience temporary discomfort due to the previous reason, and 6% of patients undergo further treatment with permanent impairment [3,4,7].…”
Section: Introductionmentioning
confidence: 99%